Vertebral Metastasis With Syringomyelia Secondary to Breast Adenocarcinoma: A Case Report and Literature Review - Ahmed Reda Abdelhalim; Hossam Tharwat Ali; Bishoy Adel Kamel Zakher; Yara Ashour (Clinical Case Reports, 2025)
ABSTRACT Syringomyelia has several possible causes, commonly including Chiari malformation, spinal cord tumors and injuries, and damage caused by lesions around the spinal cord. A 34‐year‐old female was diagnosed with primary breast cancer and vertebral metastasis and was initiated on an extensive regimen of chemotherapy and radiotherapy. A few months later, she developed numbness and weakness in her lower limbs, and she was concluded to have syringomyelia with surrounding atrophic myelopathy along with vertebral metastasis. Patients developing neurological symptoms following radiotherapy or chemotherapy should be thoroughly evaluated, and further cases should be reported in the literature.